Agronomic performance of grapevines with and without virus symptoms, and molecular comparison of viral isolates - Nascimento, Monique Bezerra; Fajardo, Thor Vinícius Martins; Eiras, Marcelo; Czermainski, Ana Beatriz Costa; Nickel, Osmar; Pio-Ribeiro, Gilvan (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the effect of viroses in symptomatic and asymptomatic grapevines on the agronomic variables related to the plant vigor and the enological quality of grapes, and to compare viral isolates obtained from these two conditions. Two experiments were performed with four cultivars. All plants were indexed by real time, reverse transcription‑polymerase chain reaction (RT‑PCR) for the probable occurrence of the following viruses: Grapevine virus A (GVA), Grapevine virus B (GVB), Grapevine virus D (GVD), Grapevine leafroll‑associated virus (GLRaV‑1 to ‑4, GLRaV‑4 strain 5), Grapevine rupestris stem pitting‑associated virus (GRSPaV), and Grapevine fleck virus (GFkV). The evaluated variables were: number of buds burst and not burst, number of branches with or without bunches, total number of buds, number of bunches, fresh bunch weight, total berry weight, rachis weight, number of berries per bunch, average berry weight, total soluble solids, total titratable acidity, pH, pruned branch weight, or rootstock and scion trunk diameters. The negative effects were more pronounced on the plants with virus symptoms; however, it was observed that plants without symptoms were also often infected. The molecular analysis of GRSPaV, GVA, and GLRaV‑2, isolates from symptomatic and asymptomatic plants, resulted in a high percentage of nucleotide identities between homologous isolates.